Penyuluhan Kompetensi Komunikasi Non Verbal Bagi Masyarakat di Desa Mekarmukti, Bandung Barat - Sri Seti Indriani; Ditha Prasanti (Universitas Mathla'ul Anwar Banten, 2017)
Non-verbal communication is the delivery of messages without words and gives meaning to verbal communication, where non-verbal communication is older than verbal communication because since we were born we have done it until the age of about 18 months, such as touch, smile, crying eyes, and so on. Without us knowing we have practiced it, it is no wonder, if we doubt someone, we are more confident in the nonverbal message (probably from his movements). This shows how important we are to learn the knowledge of non-verbal communication. This is what underlies the author performs Community Service (PKM) with the title